(untitled) (KULT_online, 2016)
In their conference proceedings fpr “Hegemonie und die Macht der Bilder“ Alice Pechrigl and Anna Schober gather various authors to tackle the topic matrix of images and their relation to the establishment of power from diverse angles. The aim of the editors is to contribute to the further theorization of the research field apart from exemplary case studies. The outcome of this endeavour is a rather sketchy, but nevertheless inspiring kaleidoscope of texts that provide new impulses to the field of research, especially from a perspective of cultural studies and theory.